Antioxidative Effects of Phenolic Compounds of Mushroom Mycelia in Simulated Regions of the Human Colon, In Vitro Study - Vamanu Emanuel; Pelinescu Diana; Avram Ionela (Polish Journal of Food and Nutrition Sciences)
Many compounds in mushrooms are biologically active; however, the in vivo actions of their metabolites are poorly understood. An in vitro system, GIS1, was used to simulate the fermentation action of microbiota in each colon region. We used MycoPo, a natural product obtained from the lyophilized mycelia of different Pleurotus ostreatus species to determine the biological effects in human-colon regions. Controls (Lentinula edodes mycelia; dried basidia of Agaricus brunnescens) were chosen to confirm the biological activity of P. ostreatus mycelia in vitro. We measured total antioxidant capacity and ferric ion-reducing antioxidant power (FRAP) in simulated colon regions to identify antioxidant compounds, and undertook in vitro gastrointestinal simulation and microbiological analyses. The highest FRAP was found for the ascending colon, and the antioxidant effect was higher when MycoPo was administered. A. brunnescens consumption resulted in low total antioxidant capacity. Polyphenol content was correlated with the antioxidant status and microbial composition of microbiota. Total polyphenolic content was higher after A. brunnescens consumption, and four types of polyphenols were identified by high-performance liquid chromatography. Major phenolic acids were gentisic acid, homogentisic acid, and small amounts of caffeic acid. The Enterobacteriaceae species populations varied greatly across the three parts of the colon. We noted a significant (p<0.01) correlation between antioxidant status in the transverse and descending colon after MycoPo administration, and A. brunnescens consumption with the number of Lactobacillus and Bifidobacteria species (R2>0.85). These data suggest a direct relationship between favorable bacterial strains and availability of bioactive compounds, with specificity for each colon region.